Pattern of Lipid Profile and Obesity among Secretariat Employees of Bangladesh - Alam, Md Billal; Ahasan, HAM Nazmul; Islam, Md Ziaul; Islam, Md Nazrul; Mohammed, Fazle Rabbi; Nur, Zannatun; Mahbub, Md. Shahriar; Faiz, Md Abul (Journal of Medicine, 2009)
Background: By the dawn of this modern era of science, the prime challenge of physician is cardiovascular diseases (CVD). The most important modifiable risk factors of CVDs are unhealthy diet, physical inactivity and tobacco use. The effects of unhealthy diet and physical inactivity include abnormal blood lipid and obesity. We tried to evaluate the lipid profile and obesity among the employees of Bangladesh Secretariat. Methods: This cross sectional type of descriptive study was carried out among 1000 employees of Bangladesh Secretariat in December, 2008. All classes of employees irrespective of age or sex were included. Body mass index (BMI) and fasting lipid profile were measured in each case. Socio-demographic variables and different related risk factors were also evaluated. Result: Out of 1000 employees with a male, female ratio of 4.75:1, 65% had sedentary life style.20.6% were smoker and only 0.05% had a history of taking alcohol regularly. 10.1% had a history of hyperlipidemia in first degree relatives. Only 2.1% were known cases of hyperlipidemia. BMI of 47% employees were in normal range with a mean 24.38 Â± 3.14 SD. Mean fasting total cholesterol, LDL, HDL and triglyceride (TG) level was found 170.65 Â± 39.37, 103.72 Â± 30.9, 36.45 Â± 5.93 and 169 Â± 97.69 SD respectively. Abnormal fasting total cholesterol, LDL, HDL and TG were found in 17.3%, 48.5%, 75.6% and 48.5% employees respectively. Â Conclusion: Dyslipidemia and obesity are two important modifiable risk factors of CVDs. Early detection and prevention of obesity and abnormal lipid profile can largely reduce morbidity and mortality and alleviate undue burden on our limited health budget. Â doi:10.3329/jom.v10i3.2007 J Medicine 2009; 10 (Supplement 1): 3-6